2020
DOI: 10.1186/s13045-020-00860-y
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical donor is preferred over matched sibling donor for pre-transplantation MRD positive ALL: a phase 3 genetically randomized study

Abstract: Background: Previous reports suggest a benefit associated with haploidentical donor transplantation (HIDT) compared to matched sibling donor transplantation (MSDT) in certain contexts, and the choice of optimal candidates warrants further investigation. Methods: We designed a prospective genetically randomized study to evaluate donor options between acute lymphoblastic leukemia (ALL) patients positive for measurable residual disease (MRD) pre-transplantation who underwent HIDT (n = 169) or MSDT (n = 39). Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 35 publications
4
55
0
Order By: Relevance
“…Moreover, the recent advance of haploidentical donor HSCT, has improved transplant-related outcomes for adults with ALL, especially older patients who are more likely to lack a matched donor [151][152][153]. This may be a particularly good option for patients with MRD-positive disease, as one prospective study showed better outcomes for haploidentical donor HSCT compared with matched sibling donor HSCT in this context [154]. In addition, the acceptable non-relapse mortality and favorable survival seen in patients older than 60 years treated with reduced-intensity conditioning (with post-HSCT OS up to 45% reported in this population) have made allogeneic HSCT a more feasible approach for older/less fit patients [155][156][157].…”
Section: Evolving Role Of Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…Moreover, the recent advance of haploidentical donor HSCT, has improved transplant-related outcomes for adults with ALL, especially older patients who are more likely to lack a matched donor [151][152][153]. This may be a particularly good option for patients with MRD-positive disease, as one prospective study showed better outcomes for haploidentical donor HSCT compared with matched sibling donor HSCT in this context [154]. In addition, the acceptable non-relapse mortality and favorable survival seen in patients older than 60 years treated with reduced-intensity conditioning (with post-HSCT OS up to 45% reported in this population) have made allogeneic HSCT a more feasible approach for older/less fit patients [155][156][157].…”
Section: Evolving Role Of Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…The study protocol was in accordance with the Declaration of Helsinki and was approved by the Institutional Review Board of Peking University. All of the cases were treated according to the transplant protocol as previously described [1,17,30] .…”
Section: Methodsmentioning
confidence: 99%
“…Donor lymphocyte infusion (DLI) was performed as described previously by our group [1,17,31] . Other methods for positive MRD intervention and relapse treatment, such as interferon-γ (IFN-γ), were administered according to our previous studies [1,17,31] .…”
Section: Methods For Mrd Intervention and Relapse Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that γδ T cells can be a predict marker of relapse after HSCT. Measurable residual disease, also known as minimal residual disease (MRD), was reported as a predictor for relapse following HSCT 90 . MRD monitoring by using TRD and TRG rearrangement was demonstrated as a useful predictor for the risk of relapse in T-ALL patients with chemotherapy 91 .…”
Section: γδ T Cells and Relapse After Hsctmentioning
confidence: 99%